Epoxy resin composition, prepreg and fiber-reinforced composite material
Patent Information
- Application Number
- JP2020570089
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-15
- Filing Date
- 2020-11-05
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-11-05
Smart Images

Figure 0007631807000003 
Figure 0007631807000004 
Figure 0007631807000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an epoxy resin composition that is suitably used for fiber-reinforced composite materials for aerospace applications, general industrial applications, sports applications, and the like, and to a prepreg and a fiber-reinforced composite material each using the epoxy resin composition. [Background technology]
[0002] Fiber-reinforced composite materials using carbon fibers, aramid fibers, or the like as reinforcing fibers are widely used, taking advantage of their high specific strength and specific elastic modulus, in structural materials for aircraft and automobiles, etc., sports materials such as tennis rackets, golf shafts, fishing rods, bicycles, and housings, general industrial applications, etc. As the resin composition used in these fiber-reinforced composite materials, thermosetting resins are mainly used from the viewpoints of heat resistance and productivity, and among them, epoxy resins are preferably used from the viewpoint of mechanical properties such as adhesion to reinforcing fibers.
[0003] In recent years, in order to apply fiber-reinforced composite materials to applications requiring further weight reduction, various physical properties need to be improved. Therefore, in order to improve various mechanical properties of fiber-reinforced composite materials, there is a demand for improvements in the elastic modulus, elongation, and strength of epoxy resins used as matrix resins. However, epoxy resin cured products with high elastic modulus are generally brittle and tend to have low elongation and strength. For this reason, it has been a technical challenge to simultaneously improve high elastic modulus, elongation, and strength.
[0004] Various studies have been conducted to improve this problem. For example, a method has been considered in which an epoxy resin having a specific structure is combined with a nanofiller to improve elastic modulus and strength (Patent Document 1). In addition, a method has been considered in which an additive is blended to improve resin strength in order to reduce the amount of dicyandiamide used as a curing agent that remains undissolved and causes defects (Patent Document 2). In addition, a method has been considered in which a liquid curing agent that is less likely to cause defects is used in resin compositions for RTM molding (Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-95675 A [Patent Document 2] International Publication No. 2019 / 181402 [Patent Document 3] JP 2014-227473 A Summary of the Invention [Problem to be solved by the invention]
[0006] Even when the technology of Patent Document 1 is used, the mechanical properties of the obtained cured resin and fiber-reinforced composite material are not sufficient, and further improvement of the mechanical properties is required. In addition, when the technology of Patent Document 2 is used, the effect of improving the resin strength is obtained, but no consideration is given to improving the elastic modulus, and a technology capable of improving both the elastic modulus and strength is required. In addition, when the technology of Patent Document 3 is used, the reactivity of the resin composition is high, and the pot life is not sufficient for use in prepreg applications.
[0007] Therefore, an object of the present invention is to provide an epoxy resin composition which can be suitably used for prepregs and fiber-reinforced composite materials and which has excellent elastic modulus, strength and pot life. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention provides an epoxy resin composition that contains the following components [A] to [C] and satisfies the following conditions (1) to (3). [A]: At least one selected from diaminodiphenylmethane type, aminophenol type, and bisphenol type Epoxy Resin [B]: Aromatic compounds that are solid at room temperature Polyamide hmm [C]: boiling point of 130°C or higher and molecular weight m of 50 or higher; 250The following compound has no epoxy group in the molecule and does not substantially have the ability to harden epoxy resins: (1): At least a part of the component [C] is selected from aliphatic polyols and alicyclic polyols, It has two or more alcoholic hydroxyl groups in its molecule. (2): The ratio C / E of the number of moles E of the epoxy groups in the component [A] to the number of moles C of the component [C] satisfying the above condition (1) is 0.01 or more and 0.20 or less. (3): The viscosity when held at 70°C for 2 hours is 5.0 times or less of the initial viscosity at 70°C.
[0009] The present invention also relates to an epoxy resin composition of the present invention. but Reinforced Fiber When impregnated with It is a prepreg.
[0010] The present invention also relates to an epoxy resin composition of the present invention. but Reinforced Fiber The component [C] is hardened in a state where the component [C] is not incorporated into the cross-linked structure but exists in the voids of the cross-linked structure. It is a fiber-reinforced composite material. Effect of the Invention
[0011] According to the present invention, an epoxy resin composition excellent in elastic modulus, strength and pot life can be obtained, which can be suitably used for prepreg and fiber-reinforced composite material applications. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a graph showing the relationship between the ratio C / E of the number of moles C of the constituent element [C] to the number of moles E of the epoxy groups in the constituent element [A] and the elastic modulus in Example 2 (C / E=0.02), Example 3 (C / E=0.05), Example 4 (C / E=0.10), Example 5 (C / E=0.16), Comparative Example 1 (C / E=0.00), and Comparative Example 8 (C / E=0.23). [Diagram 2]FIG. 2 is a graph showing the relationship between the ratio C / E of the number of moles C of the component [C] to the number of moles E of the epoxy groups in the component [A] and the strength in Example 2 (C / E=0.02), Example 3 (C / E=0.05), Example 4 (C / E=0.10), Example 5 (C / E=0.16), Comparative Example 1 (C / E=0.00), and Comparative Example 8 (C / E=0.23). [Diagram 3] 3 is a diagram showing the relationship between the molecular weight m of the component [C] and the elastic modulus in Example 1 (m=62), Example 4 (m=76), Example 6 (m=118), Example 7 (m=102), Comparative Example 1, and Comparative Example 6 (m=258). Note that Comparative Example 1, which does not contain the component [C], is plotted at the position of m=0. [Figure 4] 4 is a diagram showing the relationship between the molecular weight m of the component [C] and strength in Example 1 (m=62), Example 4 (m=76), Example 6 (m=118), Example 7 (m=102), Comparative Example 1, and Comparative Example 6 (m=258). Note that Comparative Example 1, which does not contain the component [C], is plotted at the position of m=0. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below. In the present invention, the term "not less than" means that the value is equal to or greater than the indicated value. The term "not more than" means that the value is equal to or smaller than the indicated value.
[0014] The resin composition of the present invention contains the components [A] to [C] as essential components. In the present invention, the term "component" refers to a compound contained in the composition.
[0015] The component [A] in the present invention is an epoxy resin. As the epoxy resin of the component [A], one containing two or more epoxy groups in one molecule is preferable because it can increase the glass transition temperature of the cured product obtained by heat curing the resin composition and improve the heat resistance. Also, an epoxy resin containing one epoxy group in one molecule may be blended. These epoxy resins may be used alone or in appropriate blends.
[0016] Examples of the epoxy resin of the component [A] include epoxy resins of diaminodiphenylmethane type, diaminodiphenylsulfone type, aminophenol type, bisphenol type, metaxylenediamine type, 1,3-bisaminomethylcyclohexane type, isocyanurate type, hydantoin type, phenol novolac type, orthocresol novolac type, trishydroxyphenylmethane type, and tetraphenylolethane type, etc. Among these, epoxy resins of diaminodiphenylmethane type, aminophenol type, and bisphenol type are particularly preferably used because of their well-balanced physical properties.
[0017] Commercially available diaminodiphenylmethane epoxy resins include ELM434 (manufactured by Sumitomo Chemical Co., Ltd.), Araldite (registered trademark) MY720 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY721 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY9512 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY9663 (manufactured by Huntsman Advanced Materials Co., Ltd.), Epotohto (registered trademark) YH-434 (manufactured by Tohto Kasei Co., Ltd.), and jER (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation).
[0018] Commercially available diaminodiphenylsulfone type epoxy resins include TG3DAS (manufactured by Mitsui Fine Chemicals, Inc.).
[0019] Commercially available aminophenol type epoxy resins include ELM120 (manufactured by Sumitomo Chemical Co., Ltd.), ELM100 (manufactured by Sumitomo Chemical Co., Ltd.), jER (registered trademark) 630 (manufactured by Mitsubishi Chemical Corporation), Araldite (registered trademark) MY0500 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY0510 (manufactured by Huntsman Advanced Materials Co., Ltd.), Araldite (registered trademark) MY0600 (manufactured by Huntsman Advanced Materials Co., Ltd.), and Araldite (registered trademark) MY0610 (manufactured by Huntsman Advanced Materials Co., Ltd.).
[0020] Commercially available bisphenol A type epoxy resins include "EPON (registered trademark)" 825 (manufactured by Mitsubishi Chemical Corporation), "Epicron (registered trademark)" 850 (manufactured by DIC Corporation), "Epototo (registered trademark)" YD-128 (manufactured by Tohto Kasei Co., Ltd.), and DER-331 and DER-332 (all manufactured by The Dow Chemical Company).
[0021] Commercially available bisphenol F type epoxy resins include "Araldite (registered trademark)" GY282 (manufactured by Huntsman Advanced Materials), "jER (registered trademark)" 806, "jER (registered trademark)" 807, "jER (registered trademark)" 1750 (all manufactured by Mitsubishi Chemical Corporation), "Epicron (registered trademark)" 830 (manufactured by DIC Corporation), and "Epotohto (registered trademark)" YD-170 (manufactured by Tohto Kasei Co., Ltd.).
[0022] The epoxy resin composition of the present invention may also contain epoxy compounds other than those mentioned above.
[0023] The component [B] in the present invention is a polyamine curing agent. The polyamine curing agent has a plurality of amino groups (including two amino groups) that can react with epoxy groups, and functions as a curing agent. The polyamine curing agent undergoes an addition reaction with the epoxy resin, during which hydroxyl groups are generated by ring-opening of the epoxy groups. A strong intermolecular interaction occurs between the hydroxyl groups generated in the crosslinked structure of the epoxy resin cured product and the component [C] described below, which makes it easier for the component [C] to be retained in the crosslinked structure, thereby improving the elastic modulus, strength, and elongation.
[0024] Examples of polyamine curing agents include aliphatic polyamines and aromatic polyamines. These polyamine curing agents may be used alone or in combination. Aromatic polyamines, especially aromatic diamines, are excellent as curing agents in that they can impart high mechanical properties and heat resistance to the epoxy resin cured product.
[0025] Classified as aromatic polyamines include diethyltoluenediamines such as 2,2'-diethyldiaminodiphenylmethane, 2,4-diethyl-6-methyl-m-phenylenediamine, 4,6-diethyl-2-methyl-m-phenylenediamine, and 4,6-diethyl-m-phenylenediamine, 4,4'-methylenebis(N-methylaniline), 4,4'-methylenebis(N-ethylaniline), 4,4'-methylenebis(N-sec-butylaniline), N,N'-di-sec-butyl-p-phenylenediamine, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfone, and 3,3'-diisopropyl-4,4'-diaminodiphenylmethane. , 3,3'-di-t-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenylmethane, and the like. Among them, 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone are preferably used because the mechanical properties of the obtained cured product are excellent. In addition, it is preferable to use a solid curing agent as the polyamine curing agent, and it is particularly preferable to use at least one of 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone, in order to suppress the increase in viscosity when the epoxy resin composition of the present invention is kept at 70°C and thereby to effectively improve the pot life.
[0026] Commercially available aromatic polyamines include Seikacure S (manufactured by Wakayama Seika Kogyo Co., Ltd.), MDA-220 (manufactured by Mitsui Chemicals, Inc.), "jER Cure (registered trademark)" WA (manufactured by Mitsubishi Chemical Corporation), and 3,3'-DAS (manufactured by Mitsui Chemicals, Inc.), "Lonzacure (registered trademark)" M-DEA (manufactured by Lonza Corporation), "Lonzacure (registered trademark)" M-DIPA (manufactured by Lonza Corporation), "Lonzacure (registered trademark)" M-MIPA (manufactured by Lonza Corporation), and "Lonzacure (registered trademark)" DETDA 80 (manufactured by Lonza Corporation).
[0027] The amount of polyamine curing agent in the present invention is preferably 0.50 or more and 1.30 or less, more preferably 0.70 or more and 1.20 or less, and even more preferably 0.80 or more and 1.10 or less, in terms of the ratio H / E between the number of moles of epoxy groups in the component [A] and the number of moles of active hydrogen in the polyamine curing agent. By setting H / E within this range, a crosslinked structure can be appropriately formed by the reaction between the epoxy resin and the polyamine curing agent, and a resin cured product excellent in strength and elongation can be obtained. In addition, by setting H / E to 0.80 or more and 1.10 or less, the amount of hydroxyl groups generated by the reaction between the epoxy resin and the polyamine curing agent becomes appropriate. As a result, the component [C] described later is easily retained in the crosslinked structure, and the effect of improving the elastic modulus, strength, and elongation can be obtained.
[0028] In the epoxy resin composition of the present invention, the ratio of the number of moles E of epoxy groups in the component [A] to the total number of moles of at least one of 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone ((total number of moles of at least one of 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone) / E) is preferably 0.50 or more and 1.30 or less. By making the ratio 0.50 or more and 1.30 or less, more preferably 0.70 or more and 1.20 or less, and even more preferably 0.80 or more and 1.10 or less, it is possible to suppress an increase in viscosity when the epoxy resin composition of the present invention is kept at 70°C, and thus to effectively improve the pot life.
[0029] The component [C] is a compound having a boiling point of 130°C or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. Here, compounds such as amines and phenols capable of addition reaction with epoxy resins, acid anhydrides capable of copolymerizing with epoxy resins, imidazoles capable of acting as self-polymerization initiators for epoxy resins, aromatic urea compounds, and tertiary amine compounds are compounds capable of hardening epoxy resins, but do not fall under the category of compounds not capable of hardening epoxy resins.
[0030] The component [C] is not incorporated into the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, but exists in the voids, and is maintained in this state even after curing. This increases the elastic modulus of the resulting epoxy resin cured product. Surprisingly, the inventors have found that by blending the component [C], an epoxy resin cured product having not only a high elastic modulus but also high elongation and high strength can be obtained. The reason for this is unclear, but the inventors believe it to be as follows. The component [C] does not have an epoxy group in the molecule and does not substantially have the ability to cure the epoxy resin, so it does not react with the epoxy resin or polyamine that form the crosslinked structure. Therefore, the component [C] is not bound by a covalent bond to the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, and is appropriately held in the voids of the crosslinked structure, so that the voids in the cured product can be effectively filled, and the elastic modulus of the cured product is increased. In addition, the inventors believe that when strain is applied to the cured product, component [C] can move freely within the crosslinked structure, thereby mitigating the strain energy leading to fracture, thereby increasing the elongation and strength of the cured product.
[0031] In addition, by making the boiling point of the component [C] 130°C or higher, more preferably 180°C or higher, it is possible to suppress the volatilization of the component [C] when the epoxy resin composition is cured, and to obtain a resin cured product or a fiber-reinforced composite material having excellent mechanical properties. Furthermore, it is possible to suppress the generation of voids and the deterioration of mechanical properties in the obtained fiber-reinforced composite material. In the present invention, the boiling point is a value at normal pressure (101 kPa). In addition, when the boiling point at normal pressure cannot be measured, a converted boiling point converted to 101 kPa using a boiling point conversion chart can be used.
[0032] The molecular weight m of the component [C] is 50 or more and 250 or less. By setting the molecular weight of the component [C] within this range, the component [C] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, and a cured product excellent in elastic modulus, strength, and elongation can be obtained. In addition, by setting the molecular weight m of the component [C] to 50 or more and 150 or less, a cured product with particularly excellent elastic modulus can be obtained. In addition, by setting it preferably to 70 or more and 110 or less, a cured product with even more excellent elastic modulus can be obtained. In addition, by setting it preferably to 50 or more and 110 or less, a cured product with especially excellent strength can be obtained. In addition, by setting it preferably to 50 or more and 90 or less, a cured product with even more excellent strength can be obtained.
[0033] At least a part of the constituent element [C] has two or more alcoholic hydroxyl groups in the molecule (condition (1)). Here, a compound having an alcoholic hydroxyl group is a compound in which hydrogen of an aliphatic hydrocarbon is replaced by a hydroxyl group, and does not include a compound having a phenolic hydroxyl group in which hydrogen of an aromatic ring is replaced by a hydroxyl group. When the constituent element [C] has an alcoholic hydroxyl group in the molecule, a strong intermolecular interaction occurs between the alcoholic hydroxyl group in the crosslinked structure formed by the constituent element [A] and the constituent element [B] and the constituent element [C], and the constituent element [C] is easily held appropriately in the void portion of the crosslinked structure, so that an excellent effect of improving elongation and strength is obtained. Furthermore, when the constituent element [C] has two or more alcoholic hydroxyl groups in the molecule, the number of points where the above-mentioned intermolecular interaction occurs in the crosslinked structure increases, and particularly excellent effects of improving elongation and strength are obtained.
[0034] Examples of the component [C] having two or more alcoholic hydroxyl groups in the molecule include 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,2-propanediol, 2-methyl-1,3-propanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 2-methyl-1,2-butanediol, 2-methyl- ethyl-2,3-butanediol, 2-methyl-1,4-butanediol, 3-methyl-1,2-butanediol, 3-methyl-1,3butanediol, 2-ethyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,2-hexanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 3,3-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 3-methyl-1,5-pentanediol 3-Methyl-2,3-pentanediol, 3-Methyl-2,4-pentanediol, 4-Methyl-1,2-pentanediol, 2-Ethyl-2-methyl-1,3-propanediol, 2,2-Dimethyl-2,4-butanediol, 2,3-Dimethyl-1,2-butanediol, 1,2-Heptanediol, 1,7-Heptanediol, 3,4-Heptanediol, 2-Propyl-2-methyl-1,3-propanediol, 2-Isopropyl-2-methyl-1,3-propanediol, 1,2-Octanediol, 1,8-Octanediol, 3,6 -Octanediol, 2-ethyl-1,3-hexanediol, 2-sec-butyl-2-butyl-1,3-propanediol, 2,2-dimethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,2-nonanediol, 1,3-nonanediol, 1,9-nonanediol, 3,6-octanediol, 2-ethyl-2-(2-methyl)propyl-1,3-propanediol, 2,2,4-trimethyl-1,6-hexanediol, 2,4,4-trimethyl-1,6-Hexanediol, 2-Butyl-2-Ethyl-1,3-Propanediol, 2,4-Diethyl-1,5-Pentanediol, 2-Methyl-1,8-Octanediol, 1,2-Decanediol, 1,10-Decanediol, 5,6-Decanediol, 3,6-Dimethyl-3,6-Octanediol, 3,7-Dimethyl-1,6-Octanediol, 3,7-Dimethyl-1,7-Octanediol, Butanetriol, Heptatriol, Trimethylolpropane, Pentaerythritol, Examples of the polyols include aliphatic polyols such as lythritol, xylitol, and sorbitol; alicyclic polyols such as cyclopentanediol, cyclopentane dimethanol, cyclohexanediol, cyclohexane dimethanol, cycloheptanediol, and cycloheptane dimethanol; polyols having an ether group such as diethylene glycol, triethylene glycol, dipropylene glycol, and tripropylene glycol; and aromatic polyols such as benzene dimethanol. These compounds may be used alone or in appropriate combination.
[0035] In the epoxy resin composition of the present invention, it is important that the ratio C / E of the number of moles E of the epoxy group in the component [A] to the number of moles C of the component [C] satisfying the condition (1) is 0.01 or more and 0.20 or less (condition (2)). By setting C / E within this range, the component [C] is appropriately held in the voids of the crosslinked structure formed by the reaction of the epoxy resin and the polyamine, and a cured product excellent in elastic modulus, strength, and elongation can be obtained. In addition, by setting the molecular weight m of the component [C] to 70 or more and 110 or less, and C / E to preferably 0.07 or more and 0.20 or less, a cured product with particularly excellent elastic modulus can be obtained. In addition, by setting the molecular weight m of the component [C] to 70 or more and 110 or less, and C / E to preferably 0.01 or more and 0.13 or less, a cured product with particularly excellent strength can be obtained. Furthermore, by adjusting the molecular weight m of the component [C] to 70 or more and 110 or less, and by adjusting C / E to preferably 0.07 or more and 0.13 or less, a cured product with particularly excellent elastic modulus and strength can be obtained.
[0036] It is also important that the viscosity of the resin composition of the present invention when kept at 70°C for 2 hours is 5.0 times or less of the initial viscosity at 70°C (condition (3)). By making this ratio (also called "viscosity increase ratio") 5.0 times or less, more preferably 3.0 times or less, and even more preferably 2.5 times or less, the viscosity change of the resin composition is small in the process of kneading the resin composition and the process of impregnating the resin composition into the reinforcing fibers, and the pot life can be extended. In addition, the variation in the flow rate of the resin composition during molding can be reduced, and the variation in the resin content contained in the fiber-reinforced composite material can be suppressed, and a fiber-reinforced composite material with stable dimensions and mechanical properties can be obtained.
[0037] The viscosity increase rate can be effectively suppressed by using, as the polyamine curing agent of component [B], an aromatic diamine that is in a solid state, particularly at least one of 3,3'-diaminodiphenyl sulfone and 4,4'-diaminodiphenyl sulfone.
[0038] The epoxy resin composition of the present invention is excellent in elastic modulus, strength and elongation, and is suitable for use as a matrix resin for fiber-reinforced composite materials. That is, the fiber-reinforced composite materials of the present invention comprise a cured product of the epoxy resin composition of the present invention and reinforcing fibers.
[0039] Methods for obtaining fiber-reinforced composite materials include methods in which reinforcing fibers are impregnated with a resin composition during a molding process, such as the hand lay-up method, the RTM method, the filament winding method, and the pultrusion molding method, and methods in which a prepreg in which reinforcing fibers have been previously impregnated with a resin composition is molded by an autoclave method or a press molding method. Among these, it is preferable to prepare a prepreg made of an epoxy resin composition and reinforcing fibers in advance, since this allows precise control of the fiber arrangement and the resin ratio, and maximizes the properties of the composite material. That is, the prepreg of the present invention is made of the epoxy resin composition of the present invention and reinforcing fibers.
[0040] The reinforcing fibers used in the prepreg and fiber-reinforced composite material of the present invention are preferably carbon fiber, graphite fiber, aramid fiber, glass fiber, etc., with carbon fiber being particularly preferred. There are no limitations on the form or arrangement of the reinforcing fibers, and for example, fiber structures such as long fibers aligned in one direction, single tow, woven fabric, knit, and braided cord are used. As the reinforcing fibers, two or more types of carbon fibers, glass fibers, aramid fibers, boron fibers, PBO fibers, high-strength polyethylene fibers, alumina fibers, silicon carbide fibers, etc. may be used in combination.
[0041] Specific examples of carbon fibers include acrylic, pitch and rayon carbon fibers, with acrylic carbon fibers having particularly high tensile strength being preferably used.
[0042] The carbon fiber can be in the form of twisted yarn, untwisted yarn, non-twisted yarn, etc., but in the case of twisted yarn, the filaments that make up the carbon fiber are not oriented parallel to one another, which can cause a decrease in the mechanical properties of the resulting carbon fiber reinforced composite material. Therefore, untwisted yarn or non-twisted yarn, which provide a good balance between the formability and strength properties of the carbon fiber reinforced composite material, are preferably used.
[0043] The tensile modulus of the carbon fiber is preferably 200 GPa or more and 440 GPa or less. The tensile modulus of the carbon fiber is affected by the crystallinity of the graphite structure constituting the carbon fiber, and the higher the crystallinity, the higher the modulus. This range is preferable because the rigidity and strength of the carbon fiber reinforced composite material are all balanced at a high level. The more preferable modulus is 230 GPa or more and 400 GPa or less, and even more preferably 260 GPa or more and 370 GPa or less. Here, the tensile modulus of the carbon fiber is a value measured according to JIS R7608 (2008).
[0044] The prepreg of the present invention can be produced by various known methods. For example, the prepreg can be produced by a hot melt method in which a resin composition is heated to reduce its viscosity without using an organic solvent and then impregnated into reinforcing fibers.
[0045] In the hot melt method, a resin composition whose viscosity has been reduced by heating can be directly impregnated into the reinforcing fibers, or a release paper sheet with a resin film can be first prepared by coating the resin composition on release paper or the like, and then a resin film can be placed on the reinforcing fiber side from both sides or one side of the reinforcing fibers, and the reinforcing fibers can be impregnated with the resin composition by heating and pressurizing.
[0046] The content of reinforcing fibers in the prepreg is preferably 30% by mass or more and 90% by mass or less. By making it 30% by mass or more, more preferably 35% by mass or more, and even more preferably 65% by mass or more, it is easy to obtain the advantages of a fiber-reinforced composite material having excellent specific strength and specific elastic modulus. In addition, when molding the fiber-reinforced composite material, it is possible to prevent the amount of heat generated during curing from becoming too high. On the other hand, by making it 90% by mass or less, more preferably 85% by mass or less, it is possible to prevent the generation of voids in the composite material due to poor resin impregnation. In addition, it is possible to maintain the tackiness of the prepreg.
[0047] The fiber-reinforced composite material of the present invention can be produced, for example, by laminating the above-mentioned prepregs of the present invention in a predetermined shape and curing the resin by applying pressure and heat. Methods for applying heat and pressure include press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc.
[0048] The fiber-reinforced composite material of the present invention can be widely used in aerospace applications, general industrial applications, and sports applications. More specifically, in general industrial applications, it is preferably used in structures such as automobiles, ships, and railway vehicles. In sports applications, it is preferably used in golf shafts, fishing rods, and tennis and badminton rackets. EXAMPLES
[0049] The present invention will be described in detail below with reference to examples. However, the scope of the present invention is not limited to these examples. The unit "parts" in the composition ratio means parts by mass unless otherwise noted. Furthermore, the measurements of various characteristics (physical properties) were performed in an environment with a temperature of 23°C and a relative humidity of 50% unless otherwise noted.
[0050] <Materials used in the Examples and Comparative Examples> (1) Component [A]: Epoxy resin "Araldite (registered trademark)" MY0600 (aminophenol type epoxy resin, epoxy equivalent: 118g / eq, number of epoxy groups: 3, manufactured by Huntsman Advanced Materials, Inc.) "jER (registered trademark)" 825 (bisphenol A type epoxy resin, epoxy equivalent: 170g / eq, number of epoxy groups: 2, manufactured by Mitsubishi Chemical Corporation) Glycidol (molecular weight: 74 g / mol, epoxy equivalent: 74 g / eq, number of epoxy groups: 1, boiling point: 167°C, manufactured by Tokyo Chemical Industry Co., Ltd.).
[0051] (2) Component [B]: Polyamine hardener 3,3'-DAS (3,3'-diaminodiphenyl sulfone, active hydrogen equivalent: 62g / eq, number of active hydrogens: 4, manufactured by Mitsui Fine Chemicals Co., Ltd.) Seikacure S (4,4'-diaminodiphenyl sulfone, active hydrogen equivalent: 62g / eq, number of active hydrogens: 4, manufactured by Wakayama Seika Kogyo Co., Ltd.) "jER Cure (registered trademark)" WA (diethyltoluenediamine, active hydrogen equivalent: 45g / eq, number of active hydrogens: 4, manufactured by Mitsubishi Chemical Corporation).
[0052] (3) Component [C]: a compound having a boiling point of 130°C or higher and a molecular weight m of 50 to 250 g / mol, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. 1,2-Ethanediol (boiling point: 197°C, molecular weight m: 62g / mol, manufactured by Tokyo Chemical Industry Co., Ltd.) 1,2-Propanediol (boiling point: 188°C, molecular weight m: 76g / mol, manufactured by Tokyo Chemical Industry Co., Ltd.) 1,2-Hexanediol (boiling point: 245°C, molecular weight m: 118g / mol, manufactured by Tokyo Chemical Industry Co., Ltd.) trans-1,2-Cyclopentanediol (boiling point: 250°C, molecular weight m: 102 g / mol, manufactured by Sigma-Aldrich Japan, LLC).
[0053] (4) Other compounds 2,4-Toluenebis(dimethylurea) ("Omicure®" U-24, manufactured by Emerald Performance Materials, LLC) Ethanol (boiling point: 78°C, molecular weight m: 46g / mol, manufactured by Tokyo Chemical Industry Co., Ltd.) 1,2-Hexadecanediol (boiling point: 356°C, molecular weight m: 258g / mol, manufactured by Tokyo Chemical Industry Co., Ltd.).
[0054] <Various evaluation methods> The epoxy resin composition of each example was measured using the following measurement methods.
[0055] (1) Three-point bending test of cured resin The uncured resin composition was degassed in a vacuum, and then heated from 30°C at a rate of 1.7°C / min in a mold set to a thickness of 2 mm using a 2 mm Teflon (registered trademark) spacer, held at 125°C for 5 hours, and then heated at a rate of 1.7°C / min to cure at 225°C for 2 hours to obtain a 2 mm thick plate-shaped cured resin. A test piece 10 mm wide and 60 mm long was cut out from this cured resin, and tested on an Instron universal testing machine (manufactured by Instron Corp.) with a span of 32 mm, a crosshead speed of 2.5 mm / min, and the number of samples n=6 according to JIS K7171 (1994). The average values of the elastic modulus, strength, and elongation were taken as the elastic modulus, strength, and elongation of the cured resin, respectively.
[0056] (2) Viscosity measurement of resin composition Using a dynamic viscoelasticity device (TA Instruments ARES-G2), the epoxy resin composition was set so that the distance between the upper and lower jigs was 1 mm using flat parallel plates with a diameter of 40 mm as the upper and lower measuring jigs, and the initial viscosity of the epoxy resin composition at 70°C and the viscosity after being held at 70°C for 2 hours while set in the device were measured in torsion mode (measurement frequency: 0.5 Hz). The viscosity after being held at 70°C for 2 hours was then divided by the initial viscosity at 70°C to obtain the viscosity increase ratio.
[0057] <Example 1> (Preparation of resin composition) A resin composition was prepared by the following method.
[0058] 100 parts of "Araldite (registered trademark)" MY0600 as the component [A] shown in Table 1 was charged into a kneading device, and heated to a target temperature of 55 to 65°C while kneading. 53 parts of 3,3'-DAS as the component [B] was added and stirred for 30 minutes. Thereafter, 5 parts of 1,2-ethanediol was added as the component [C] and stirred for an additional 10 minutes to obtain a resin composition.
[0059] At this time, the ratio H / E of the number of moles H of active hydrogen in component [B] to the number of moles E of epoxy groups in component [A] was 1.00. In addition, the ratio C / E of the number of moles C of component [C] to the number of moles E of epoxy groups in component [A] was 0.10. In addition, the molecular weight m of component [C] was 62.
[0060] The resin composition thus obtained was subjected to a three-point bending test of the cured resin, and the elastic modulus was 5.1 GPa, the strength was 225 MPa, and the elongation was 5.9%. Compared with Comparative Example 1 (not containing component [C]) described later, excellent elastic modulus, strength, and elongation were obtained. In addition, the viscosity after being kept at 70°C for 2 hours was 2.2 times the initial viscosity at 70°C, and the pot life was sufficient.
[0061] <Examples 2 to 12> The components [A], [B] and [C] were mixed in the same manner as in Example 1 above according to the mixing ratios in Tables 1 and 2 to obtain a resin composition.
[0062] The results of various measurements in the examples are shown in Tables 1 and 2. Even when the formulation of the resin composition was changed as in Examples 2 to 12, excellent elastic modulus, strength, and elongation of the cured resin were obtained. The viscosity increase ratio was also good.
[0063] <Comparative Examples 1 to 9> The components [A] and [B] or their substitutes (and [C] or their substitutes) were blended in the same manner as in Example 1 above according to the blending ratios in Table 2 to obtain resin compositions.
[0064] No equivalent to the component [C] was blended in Comparative Example 1. Comparing Comparative Example 1 with Example 1, it is clear that the incorporation of the component [C] improved the elastic modulus, strength, and elongation of the cured resin material, and in particular the strength and elongation were dramatically improved.
[0065] Comparative Example 2 also does not contain anything equivalent to the component [C]. Comparing Comparative Example 2 with Example 12, it is clear that the incorporation of the component [C] also dramatically improves the elastic modulus and strength of the cured resin.
[0066] In Comparative Example 3, 2,4-toluenebis(dimethylurea) was blended instead of the component [B], and no equivalent to the component [C] was blended. In Comparative Example 4, 2,4-toluenebis(dimethylurea) was blended instead of the component [B], and 1,2-propanediol was blended as the component [C]. Comparing Comparative Example 3 with Comparative Example 4, it can be seen that blending the component [C] in the absence of the component [B] does not contribute to a dramatic improvement in the elastic modulus or strength, but comparing Example 4 with Comparative Example 1, it can be seen that the elastic modulus or strength is dramatically improved by using a polyamine curing agent as the component [B] and combining the component [C].
[0067] In Comparative Example 5, ethanol was blended in place of the component [C]. Ethanol does not satisfy the conditions of the component [C], that is, the boiling point of 130° C. or higher and the molecular weight m of 50 to 250. Comparing Comparative Example 5 with Example 1, it is found that blending the component [C], which satisfies the requirements of a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, improves the elastic modulus, strength, and elongation of the obtained cured resin material.
[0068] In Comparative Example 6, 1,2-hexadecanediol was blended in place of the component [C], but the 1,2-hexadecanediol did not satisfy the condition that the molecular weight m of the component [C] is 50 or more and 250 or less. Comparing Comparative Example 6 with Example 1, it is found that the elastic modulus, strength, and elongation of the obtained cured resin product are improved when the component [C] satisfies the above-mentioned condition.
[0069] In Comparative Example 7, glycidol was used instead of the component [C]. Glycidol has an epoxy group in the molecule. Comparing Comparative Example 7 with Example 1, it can be seen that the elastic modulus, strength, and elongation of the obtained cured resin are improved by the component [C] not having an epoxy group in the molecule.
[0070] In Comparative Example 8, the number of moles E of the epoxy group in the component [A] and the number of moles C of the component [C] do not satisfy the condition that they are 0.01 or more and 0.20 or less. Comparing Comparative Example 8 with Example 1, it is found that satisfying the above condition improves the elastic modulus, strength, and elongation of the obtained cured resin material.
[0071] In Comparative Example 9, the epoxy resin composition does not satisfy the condition that the viscosity when kept at 70°C for 2 hours is 5.0 times or less of the initial viscosity at 70°C. Therefore, the composition had a large increase in viscosity during the step of mixing the epoxy resin and a short pot life. Comparing Comparative Example 9 with Example 1, it is clear that by satisfying the above condition, the resulting resin composition has a long pot life and is easy to handle.
[0072] Here, comparing Example 2, Example 3, Example 4, Example 5, Comparative Example 1, and Comparative Example 8, they are epoxy resin compositions containing the same constituent element [A], constituent element [B], and constituent element [C], and only the amount of the constituent element [C] is different. The relationship between the ratio C / E of the number of moles C of the constituent element [C] to the number of moles E of the epoxy group of the constituent element [A] and the elastic modulus is shown in FIG. 1, and the relationship between the ratio C / E and the strength is shown in FIG. 2. From FIG. 1 and FIG. 2, it can be seen that in the epoxy resin composition of the present invention, when C / E is 0.01 or more and 0.20 or less, a cured product excellent in elastic modulus, strength, and elongation can be obtained. In addition, when C / E is 0.07 or more and 0.20 or less, a cured product having particularly excellent elastic modulus can be obtained, and when C / E is 0.01 or more and 0.13 or less, a cured product having particularly excellent strength can be obtained.
[0073] Furthermore, comparing Example 1, Example 4, Example 6, Example 7, Comparative Example 1, and Comparative Example 6, they are epoxy resin compositions containing the same constituent element [A] and constituent element [B] in the same mixing ratio, but differ in the type or presence of the constituent element [C] or an alternative to it. The relationship between the molecular weight m of the constituent element [C] and the elastic modulus is shown in FIG. 3, and the relationship between the molecular weight m and the strength is shown in FIG. 4. From FIGS. 3 and 4, it can be seen that in the resin composition of the present invention, when the molecular weight m of the constituent element [C] is 50 to 150, a cured product having particularly excellent elastic modulus can be obtained. It can also be seen that when the molecular weight m of the constituent element [C] is 50 to 110, a cured product having particularly excellent strength can be obtained.
[0074] [Table 1]
[0075] [Table 2]
Claims
1. An epoxy resin composition comprising the following components [A] to [C] and satisfying the following conditions (1) to (3): [A]: At least one epoxy resin selected from diaminodiphenylmethane type, aminophenol type, and bisphenol type. [B]: Aromatic polyamine that is solid at room temperature [C]: A compound having a boiling point of 130° C. or higher and a molecular weight m of 50 to 250, which does not have an epoxy group in the molecule and does not substantially have the ability to harden epoxy resins. (1): At least a part of the component [C] is selected from aliphatic polyols and alicyclic polyols and has two or more alcoholic hydroxyl groups in the molecule. (2): The ratio C / E of the number of moles E of the epoxy groups in the component [A] to the number of moles C of the component [C] satisfying the above condition (1) is 0.01 or more and 0.20 or less. (3): The viscosity when held at 70°C for 2 hours is 5.0 times or less of the initial viscosity at 70°C.
2. 2. The epoxy resin composition according to claim 1, wherein the component [B] is an aromatic diamine that is solid at room temperature.
3. 3. The epoxy resin composition according to claim 1, wherein the ratio H / E of the number of moles E of epoxy groups in the component [A] to the number of moles H of active hydrogen in the component [B] is 0.50 or more and 1.30 or less.
4. A prepreg comprising reinforcing fibers impregnated with the epoxy resin composition according to any one of claims 1 to 3.
5. A fiber-reinforced composite material obtained by impregnating reinforcing fibers with the epoxy resin composition according to any one of claims 1 to 3 and curing the composition in a state in which the component [C] is present in voids in the cross-linked structure without being incorporated into the cross-linked structure.
Citation Information
Patent Citations
Epoxy-based adhesive, cover lay, prepreg, metal-clad laminate, and printed wiring board
JP2008095013A
Aqueous emulsion epoxide composition curable below freezing temperature
JP2010077176A
Epoxy resin composition for composite material, fiber-reinforced composite material, and methods for producing the same
JP2014227473A
Accelerator composition
JP2017535652A
Epoxy resin composition, and molding, prepreg and fiber-reinforced plastic prepared therewith
JP2018095675A